The Capital Investment Structure of the Medicine Sector in Bangladesh - Jahan Tithi, Esrat; Al Mobarak, Abdullah; Parvin, Naznin; Hanif, Abu; Ullah, Lokiat; Ashraf, Musfiqa; Nawar Duti, Nanziba; Al Masood, Mohammad Abdullah; Kaium, Abdul; Zaohara, Joynab (Medicine Today, 2025)
The capital investment structure of the medicine sector in Bangladesh plays a pivotal role in determining the industry's financial resilience, research capabilities, and global competitiveness. This study applies a mixed-methods research design to comprehensively analyze the capital composition, financing strategies, and investment challenges facing pharmaceutical companies operating in Bangladesh. Quantitative analysis is conducted on panel data of 10 leading firms from 2014 to 2023, focusing on debt-equity ratios, return on assets (ROA), return on equity (ROE), and long-term capital trends. Qualitative data from interviews with industry experts and financial officers provide insights into decision-making processes, risk management, and investor behavior. Findings reveal a significant preference for equity over debt, with many companies leveraging internal funding and public equity rather than bank loans or venture capital. Institutional barriers, high interest rates, and policy inconsistencies have discouraged debt financing and foreign direct investment (FDI). Additionally, regulatory constraints and a weak capital market infrastructure limit the expansion of investment opportunities in research and development (R&D). The study concludes with strategic recommendations including development of sector-specific credit instruments, enhancement of IPO mechanisms, incentivization of private equity and venture capital, and the creation of favorable regulatory frameworks. By aligning capital investment strategies with global best practices, Bangladesh’s medicine sector can achieve long-term financial sustainability and innovation-driven growth. Medicine Today 2025, Vol.37 (2): 269-273